The Nutritional Status Conseling of Toddler in The Practice of Midewife Independent Siti Rahayu, S.Tr.Keb - Reviana, Riska; Ghita, Dwi; Rizki, Andi Mustika Fadillah (Journal of Evidence-Based Community Health, 2024)
Good nutrition is needed in their early life. The first five years of life play a major role in physical development and brain development, so good nutrition is very important at this age. Toddler age is the age group that most often experiences malnutrition. Malnutrition in toddlers can have an unavoidable negative impact, where the worst manifestations can cause death. The purpose of this activity is to provide knowledge about nutrition in toddlers so that the community can be motivated to improve nutrition in toddlers. The implementation method used lectures, discussions, and questions and answers. The results of this activity obtained that residents who attended the counseling event understood and understood about nutrition in toddlers, managing food and types of food that contain nutrition in toddlers. The evaluation and impact of this activity are mothers who have toddlers in the area of PMB Siti Rahayu, S.Tr.Keb (± 30 people), the process is carried out by looking at the participants' responses through questions asked or feedback given in the discussion.